2018
DOI: 10.3389/fimmu.2018.01660
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3+ T Follicular Helper Cells Induced by Co-Administration of RTS,S/AS01B and Viral-Vectored Vaccines Are Associated With Reduced Immunogenicity and Efficacy Against Malaria

Abstract: A malaria vaccine strategy targeting multiple lifecycle stages may be required to achieve a high level of efficacy. In two Phase IIa clinical trials, we tested immunogenicity and efficacy of RTS,S/AS01B administered alone, in a staggered regimen with viral-vectored vaccines or co-administered with viral-vectored vaccines. RTS,S/AS01B induces high titers of antibody against sporozoites and viral-vectored vaccines ChAd63 ME-TRAP and MVA ME-TRAP induce potent T cell responses against infected hepatocytes. By comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 54 publications
3
23
1
Order By: Relevance
“…The successful combination of the two vaccines contrasts with previous studies where the combination of different viral vectored malaria vaccines did result in strong immune interference (23, 24) and the combination of RTS,S/AS01 with a viral vector PEV (ChAd63/MVA ME-TRAP) failed to improve vaccine efficacy when compared to the two vaccines administered individually and reduced immunogenicity and efficacy against malaria (25). This success might be attributed to shared characteristics and modes of action of RTS,S/AS01 and Pfs25-IMX313.…”
Section: Discussioncontrasting
confidence: 66%
“…The successful combination of the two vaccines contrasts with previous studies where the combination of different viral vectored malaria vaccines did result in strong immune interference (23, 24) and the combination of RTS,S/AS01 with a viral vector PEV (ChAd63/MVA ME-TRAP) failed to improve vaccine efficacy when compared to the two vaccines administered individually and reduced immunogenicity and efficacy against malaria (25). This success might be attributed to shared characteristics and modes of action of RTS,S/AS01 and Pfs25-IMX313.…”
Section: Discussioncontrasting
confidence: 66%
“…Using in vitro assays, it was also shown that this combination of vaccines exhibited similar functional activity in TB and sporozoite inhibition. Using in vivo assays, our results from mice immunized with the mixture of single-antigen formulations are in line with those of this previous study, in contrast with the studies that found immune interference or reduced efficacies for combinations of several other malaria vaccines (11, 41, 42).…”
Section: Discussionsupporting
confidence: 91%
“…Further highlighting the importance of specific Th2-cTfh targeting in vaccine optimization, the coadministration of viral vectored vaccines with RTS,S skewed the cTfh cell response toward Th1-cTfh cell activation, to the detriment of functional antibody induction and vaccine effi-cacy. 49 In contrast, multiple studies have shown that Th1-Tfh cells are associated with antibody induction to viral infections and vaccinations, including SARS-CoV-2, [16][17][18][19] highlighting that distinct vaccine approaches may be required for malaria vaccines compared to viral pathogens.…”
Section: Discussionmentioning
confidence: 99%